Analisis Implementasi PSAK No. 45 Tentang Pelaporan Keuangan Organisasi Nirlaba (Studi Kasus di Rumah Sakit Umum Aminah Blitar) - Irma Meiliana; Slamet Fauzan; Woldy Zulov; Farida Yanti (Universitas Widyatama, 2023)
Hospitals are an important part of social and health organizations that have the task of providing comprehensive health services, including preventive and curative services. An important source of information that can be used by various parties in an entity, especially hospitals, is financial reports. Hospital financial reports can be used both for management decisions and for outsiders. So that financial reports must be prepared properly so that they can be used as best as possible for the interests of stakeholders. The accounting standard that applies to hospitals that regulates the process of preparing financial reports is PSAK No. 45. The purpose of this study is to evaluate and analyze the level of compliance of hospitals in preparing and presenting financial reports and identify the reasons that influence the preparation of financial reports in hospitals. This research was taken at Aminah Blitar General Hospital. The results of the study show that at the Aminah Blitar General Hospital, it is still found that the preparation of financial reports is not in accordance with the provisions of PSAK No. 45.